Fresh and Mechanical Characteristics of Eco-efficient GPC Incorporating Nano-silica: An Overview - Sharif, Hiwa Hamid (Kurdistan Journal of Applied Research, 2021)
Nanotechnology can be regarded as one of the most active studies regions with both novel technological know-how and useful packages which have gradually received attention, especially over the past two many years. The nanotechnology development offers new performance to the materials. Recently efforts have been made to incorporate nanoparticles in construction materials to enhance properties and produce concrete with improved performance. progress in the improvement of geopolymer concrete is fast becoming a feasible alternative to conventional cement-based totally concrete because geopolymer concrete is measured as an eco-efficient green concrete that consumes a large quantity of commercial and agro byproduct substances consisting of fly ash, floor granulated blast furnace slag, rice husk ash. To improve the overall performance of geopolymer concrete several methods have been investigated including using nanomaterials to enhance the chemical reactivity of the geopolymer concrete mixture and provide fine particles to fill nanopores and voids. In this paper, a state-of-the-art review was carried out on the impact of nano-silica inclusion on the fresh and the mechanical characteristics of geopolymer concrete. So that current and The majority of the most current studies previously published were investigated to draw attention to the influences of nano-silica on the workability, compressive strength, splitting tensile strength, and flexural strength. Based on the analyzed data, the incorporation of nano-silica affected the fresh properties adversely while improves the mechanical performance up to the appropriate dosage of geopolymer concrete.